2020
DOI: 10.32479/ijeep.9439
|View full text |Cite
|
Sign up to set email alerts
|

A Forecasting Model on Carrying Capacity for Government's Controlling Measure Under Environmental Law in Thailand: Adapting Non-Recursive Autoregression Based on the Var-X Model

Abstract: This research aimed to analyze the relationship of causal factors and forecast CO 2 emissions for a 15 years period from 2020 to 2034 by applying a non-recursive autoregression vector autoregression with an exogeneous model (Non-Recursive Var-X model). The Non-Recursive Var-X model has been made available for use in long-term forecasting (2020-2034), particularly in regards to the implementation of the 'Industry 4.0' policy of the Thai government. The study found that the results of the Thai government's effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The main difference between the two types holds between element variables of the FAs. The confirmatory FA is the FA in which its element variable has been pre-defined for the FA (measurement variables), whereas the explanatory FA generates FA variables from measurement variable groups without variable specification (Sutthichaimethee and Ariyasajjakorn, 2020).…”
Section: The Materials and Methodsmentioning
confidence: 99%
“…The main difference between the two types holds between element variables of the FAs. The confirmatory FA is the FA in which its element variable has been pre-defined for the FA (measurement variables), whereas the explanatory FA generates FA variables from measurement variable groups without variable specification (Sutthichaimethee and Ariyasajjakorn, 2020).…”
Section: The Materials and Methodsmentioning
confidence: 99%
“…Ultimately, it may not be possible to rectify the situation, as environmental systems often take many years to restore to their original state and sometimes cannot be restored at all. Additionally, the government must have a key strategy for developing the country towards a green economy that is most suitable and comprehensive, leading Thailand toward a promising future in line with sustainability goals (Sutthichaimethee, Ariyasajjakorn, 2020 Hence, an extensive review of research work both within the country and abroad was conducted and found that Thailand lacks research from the perspective of the research problem discussed. The few research efforts conducted within the country often take a narrow viewpoint on specific aspects, which may not contribute effectively to the formulation of national strategies.…”
Section: Introductionmentioning
confidence: 99%